A New Process for the Recovery of Iron, Vanadium, and Titanium From Vanadium Titanomagnetite - S. Y. Chen (The Southern African Institute of Mining and Metallurgy, 2014)
A new process comprising metallizing reduction, magnetic separation, and electroheat melting separation is proposed with the aim of achieving high recoveries of iron, vanadium, and titanium from vanadium titanomagnetite. The effects of magnetic intensity, reduction temperature, reduction time, carbon ratio, and coal particle size on the efficiency of reductionmagnetic separation were investigated, the reaction mechanisms elucidated by SEM and EDS analysis, and the optimal process parameters established. Recoveries of up to 80.08% for titanium, 95.07% for iron, and 71.60% for vanadium were achieved. The reduction sequence is shown to be: Fe2O3 ? Fe3O4 ? FeO ? Fe; Fe2TiO5 ? Fe2TiO4 + TiO2 ? Fe + FeTiO3 ? Fe + FeTi2O5 ? Fe + TiO2.